A study of surgical profile of patients undergoing appendectomy - Dhruv, Kamlesh; Meshram, Sunita; Agrawal, Sujan Narayan (International Surgery Journal, 2017)
Background: The most common cause of acute abdomen in surgical is appendicitis. Among the surgeries of abdomen performed all over the world, appendectomy is the most common operation performed. Many studies have shown variations of age, gender in acute appendicitis as well as the seasonal variations in the occurrence of acute appendicitis, although the cause is not found yet. Objective was to study the surgical profile of patients undergoing appendectomy. Methods: A total of 302 patients who have undergone appendectomy were included in the present study which was hospital based cross sectional study. The study was carried out for two years at Osmania General Hospital, Hyderabad, India. Permission from Institutional Ethics Committee permission was obtained. From each and every patient included in the study, initially Informed individual consent was taken. Results: The incidence of appendicitis is much more in females i.e. 60% compared to only 40% in males. Appendicitis was most common in younger age groups of below 30 years of age. As the age increased the incidence of appendicitis decreased. From 83.2% at 30 or less than 30 of age it drastically dropped down to 15.9% in the age group of 30-49 years and in the age group of 50 and above, the incidence of appendicitis came down to less than one percentage. Only three cases were recorded above the age of 50 years. Conclusions: Present study revealed more rates in females. The disease was more common in younger age groups. The most common presenting symptom was abdominal pain. Presence of abdominal mass was absent in the present study.